EFEKTIVITAS MODEL PEMBELAJARAN VISUALIZATION AUDITORY KINESTHETIC (VAK) TERHADAP PEMAHAMAN KONSEP MATEMATIS BERDASARKAN KLASIFIKASI SELF-EFFICACY SEDANG DAN RENDAH - Muthiah Miftahul Jannah; Nanang Supriadi; Fraulein Intan Suri (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
Understanding mathematical concepts is one of the mathematical skills that must be mastered in learning mathematics. Self-efficacy is a feeling of confidence to solving a problem. This type of research is Quasi Experimental Design. The purpose of this study are to find out the Visualization Auditory Kinesthetic (VAK) learning model is more effective than conventional learning models, to find out the differences between students who have self-efficacy moderate and low on understanding mathematical concepts, and to know the interaction learning models and self-efficacy to wards understanding mathematical concepts. The population in this study were VII grade students of MTsN 2 Bandar Lampung, with research samples namely VII A as the experimental class and VII I as the control class. Data analysis techniques used normality test with Liliefors test and homogeneity test with Bartlett test. The hypothesis test used is a two-way unequal cell ANAVA test and a further test using a double comparative test using the Scheffe method. Based on the analysis and discussion of the calculation of research data, it was concluded that: First, mathematics learning using learning models was visualization auditory kinesthetic more effective than conventional learning models for understanding mathematical concepts. Second, understanding mathematical concepts of students who have self-efficacy moderate is better than low. Third, the results of the analysis show that there is no interaction between the learning model and the classification of self-efficacy to wards understanding mathematical concepts.